2017
DOI: 10.15406/jmen.2017.04.00120
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic Efficiency of Blue Green Algae on Probiotics Microorganisms

Abstract: Blue green algae also called cyanobacteria are considered to be the photosynthetic prokaryotes. Their similarities with both higher plants and simple bacteria have made them ideal model systems for intensive research in varied spheres of biology. Their role in nitrogen fixation is well known but their role as prebiotics to support the growth of probiotic bacteria is an upcoming field of study. Prebiotics includes indigestible carbohydrates mainly oligosaccharides that benefit the host organism by selectively s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 30 publications
0
18
0
3
Order By: Relevance
“…Previous studies have shown that Arthrospira platensis has a positive effect upon viability of such bacteria as Lactobacillus casei , Streptococcus thermophilus , Lactobacillus acidophilus, and Bifidobacteria when part of the intestinal flora [18,143,152,153,154], while such pathogenic bacteria as Proteus vulgaris , Bacillus subtilis and Bacillus pumulis have been suppressed during in vitro studies. When added to yoghurt, Spirulina sp.…”
Section: Microalgae As Prebioticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that Arthrospira platensis has a positive effect upon viability of such bacteria as Lactobacillus casei , Streptococcus thermophilus , Lactobacillus acidophilus, and Bifidobacteria when part of the intestinal flora [18,143,152,153,154], while such pathogenic bacteria as Proteus vulgaris , Bacillus subtilis and Bacillus pumulis have been suppressed during in vitro studies. When added to yoghurt, Spirulina sp.…”
Section: Microalgae As Prebioticsmentioning
confidence: 99%
“…promoted growth of L. acidophilus and Bifidobacteria, while Isochrysis galbana , characterized by high concentrations of both soluble and insoluble fibers, appears promising as a prebiotic. This was concluded from the increase in the number of lactic acid bacteria in the feces of rats, when previously treated with the said microalgae [18,38,52,143].…”
Section: Microalgae As Prebioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prebiotik bersifat menstimulasi pertumbuhan mikroba nonpatogenik pada saluran pencernaan sehingga diharapkan penyerapan nutrisi oleh saluran pencernaan menjadi lebih baik dan produktivitas menjadi optimal (Haryati, 2011). Salah satu bahan yang berpotesi sebagai prebiotik yaitu Spirulina platensis (Gupta et al, 2017).…”
Section: Pendahuluanunclassified
“…platensis memiliki kandungan oligosakarida berupa mannosa dan rhamnosa yang diketahui dapat menstimulasi pertumbuhan mikroba nonpatogenik (Gupta et al, 2017). Bhowmik et al (2009) (Jamil et al, 2015).…”
Section: Pendahuluanunclassified